PROPERTIES OF SURFACTANTS AND THEIR APPLICATION IN INDUSTRY - Біліщук, Віктор; Витвицька, Лідія; Чуйко, Мирослава; Криницький, Олександ (SWorldJournal, 2024)
The article states that surfactants reduce the surface energy at the interface of phases, which has positive properties when they are used as part of detergents, cosmetic and pharmaceutical preparations, and technological fluids. The surface activity of